Visibility of Blockchain Technology Application in Zakat Institutions in Lampung Province - Anggoro Sugeng; Carmidah; Aulia Ranny Priyatna (Jurnal Internasional Ekonomi Islam, 2026)
Objective: This study aims to analyze the visibility of blockchain technology implementation in zakat institutions in Lampung Province by examining transparency, accountability, accessibility, and institutional readiness for blockchain adoption. Method: This research employs a qualitative descriptive-analytical approach. Data were collected through semi-structured interviews, observations, and document analysis involving zakat institution administrators, muzakki, and mustahiq from BAZNAS, LazisMU, LazisNU, and Baitul Maal Hidayatullah (BMH) in Bandar Lampung and Metro City. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Results: Zakat institutions in Lampung Province have demonstrated progress in improving transparency, accountability, and accessibility through digital platforms, institutional audits, and periodic reporting. However, blockchain technology has not yet been fully implemented, despite strong stakeholder interest and positive perceptions of its potential benefits. The main challenges identified include limited stakeholder understanding, inadequate digital infrastructure, and the absence of integrated implementation policies. Implications: The findings suggest that accelerating blockchain adoption through stakeholder education, institutional capacity building, and technological integration could significantly enhance public trust, operational efficiency, and the sustainability of Islamic philanthropic institutions. Originality or Novelty: The novelty of this study lies in the development of a blockchain visibility perspective in zakat management by integrating three dimensions of visibility: information availability, information-sharing consent, and third-party accessibility, within the context of Islamic philanthropic institutions at the regional level in Indonesia. This study also provides empirical evidence regarding the readiness and challenges of blockchain adoption in zakat institutions in Lampung Province.